Combination of Modafinil and d-amphetamine for the Treatment of Cocaine Dependence: A Preliminary Investigation - Schmitz, Joy M.; Rathnayaka, Nuvan; Green, Charles; Moeller, F Gerard; Dougherty, Anne E.; Grabowski, John (Frontiers in Psychiatry, 2012)
Background: Two stimulant medications, modafinil and d-amphetamine, when tested individually, have shown safety and efficacy for treatment of cocaine addiction. We hypothesized that the combination of modafinil and d-amphetamine, at low doses, would show equivalent or greater benefit in reducing cocaine use compared to higher doses of each individual medication or placebo. Methods: Sixteen week, randomized, parallel-group design with four treatment arms comparing placebo to modafinil 400 mg; d-amphetamine 60 mg; modafinil 200 mg plus d-amphetamine 30 mg. Primary outcome variables, retention and cocaine use, were analyzed on the sample of 73 participants who received the first dose of the study medication. Results: Retention rates did not differ between groups and were generally low, with 40% remaining in treatment at week 12 and 20% at week 16. Participants receiving the combination of modafinil and d-amphetamine showed a trend of increased cocaine use over time with a corresponding low Bayesian probability of benefit (33%). Relatively better cocaine outcomes were observed in the placebo and d-amphetamine only groups. The study medications were generally well-tolerated with few adverse effects, yet rates of adherence were suboptimal (≤ 80%). Conclusion: Data from this preliminary investigation fail to provide evidential support for conducting a larger study of this dual-agonist medication combination for treatment of cocaine dependence.